Bandung at 60: new insights and emerging forces. 60 Years after the 1955 Bandung Asian-African Conference - (:unkn) unknown (My University, 2015)
2015 is the year of the 60th anniversary of the 1955 Bandung Asian-African Conference. Several manifestations of commemoration of this turning point of world history were organised along the year 2014-2015 in diverse countries: China, Ecuador, France, Ghana, Indonesia, Nepal, Netherlands, Tunisia, USA,… Why all these commemorations? What do they reveal? What are their outcomes? This book tries to answer these questions by presenting selected papers coming from those diverse manifestations. The papers are written by eighteen academics from Africa, Asia, Latin America, Europe and USA. They are: Adams Bodomo (Ghana/Austria), Aziz Salmone Fall (Egypt/Senegal/Canada), Beatriz Bissio (Uruguay/Brazil), Darwis Khudori (Indonesia/France), Erebus Wong (China), István Tarrósy (Hungary), Jason E. Strakes (Georgia/USA), Lau Kin Chi (China), Lazare Ki-Zerbo (Burkina Faso/France), Lin Chun (China/UK), Manoranjan Mohanty (India), Mérick Freedy Alagbe (Congo/France), Naoko Shimazu (Japan/UK), Noha Khalaf (Palestine/France), Seema Mehra Parihar (India), Sit Tsui (China), Trikurnianti Kusumanto (Indonesia/Netherlands), Wen Tiejun (China).
Keywords: African Research